Woong Rame Beach Marketing Communication Strategy In Increasing Tourist Intensity - Alfan Syihab; Muhammad Alfikri (LEGAL BRIEF, 2022)
This study aims to determine the marketing communication strategy of Woong Rame Beach in increasing the intensity of tourists. In this digitalization era, marketing communication has changed its strategy. This causes the management of Woong Rame Beach to revise the strategy so that tourists can afford it. This study uses a qualitative method with a descriptive approach. The data collection techniques used are interviews, observation and documentation. This study shows that Woong Rame Beach uses a sales call technique, namely direct visits to the government's target market, several companies, schools, communities, and communities. Then, sales blitz (direct door to door visits) digital marketing, exhibitions, and brand collaboration. This technique is considered quite effective because of the increase in the intensity of tourists.